Political Culture of Coastal Society in the Hinterland Area of Batam City - Ayu Pratiwi, Diah; Enita Puspita Sari, Meri (International Journal of Engineering and Technology, 2018)
This research examines the political culture of coastal communities in the face of Simultaneous Regional Elections of 2015 in Batam City. The purpose of this research is to analyze the types of political culture and the participation of coastal society in political activities, especially elections, because there is no research that discusses the political culture of coastal society in particular. Research that discusses the political life of coastal society has not been discussed, especially how the role and views of society on political life and government. In fact, coastal society are groups that will be affected and feel the consequences of these political activities. This research uses qualitative method. The respondents are selected by purposive sampling technique and data obtained by observation and in-depth interview. The findings in this study indicate that the type of coastal society culture is included in the type of participant political culture, in which the level of participation society in Simultaneous Regional Elections of 2015 is quite high and their knowledge on political activity is sufficient.Â Â